Association between lymphocyte to high-density lipoprotein cholesterol ratio and insulin resistance and metabolic syndrome in US adults: results from NHANES 2007–2018 - Junwei Guo; Kelibinuer Mutailipu; Xin Wen; Jiajing Yin; Hui You; Shen Qu; Haibing Chen; Le Bu (Lipids in Health and Disease)
Abstract Background Insulin resistance (IR) and metabolic syndrome (MetS) are significant global health challenges that increase the risk of various chronic diseases. The lymphocyte-to-high-density lipoprotein cholesterol ratio (LHR) has emerged as a novel inflammatory metabolic marker. The present study focused on evaluating the association between the LHR and both IR and MetS. Methods We analyzed data from 14,779 adults aged ≥ 20 years from the National Health and Nutrition Examination Survey (2007–2018). To investigate the relationship between LHR and both IR and MetS, we conducted multivariable logistic regression analyses. The reliability of the results was validated through both stratified and sensitivity analyses. Furthermore, we thoroughly examined possible nonlinear associations by implementing a restricted cubic spline in conjunction with a threshold effect analysis. Results Compared to the lowest LHR quartile, individuals in the highest quartile indicated significantly increased prevalence of IR (odds ratio = 3.72, 95% confidence intervals: 3.01–4.59) and MetS (odds ratio = 11.38, 95% confidence intervals: 8.85–14.63) in fully adjusted models. Subgroup analyses demonstrated that the association between the LHR and IR remained consistent across all subgroups, with no significant interaction effect observed. However, the association between LHR and MetS was more pronounced in female participants. Restricted cubic spline analyses revealed nonlinear associations between LHR and both IR and MetS. The threshold effect analyses identified inflection points at 0.055 for these non-linear relationships. Conclusions An elevated LHR was positively associated with the prevalence of IR and MetS, indicating its promising role in early screening and disease prevention through biological monitoring.